Parámetros para procedimiento de diseño y construcción de la conexión viga “I” de sección reducida – columna cajón rellena para edificaciones sismorresistentes. - Vallejo Ricaurte, Marco Paúl (2021)
The connection reduced beam section and concrete filled box column is an unqualified connection, however, it is one of the most used in Ecuador according to several authors, the same authors who demonstrated that it has a good performance as long as it complies with several design and construction requirements present in American codes, which were compiled in this work. In this thesis was elaborated a check list with relevant information that was used in three buildings in our country to recognize errors in the connection studied, such as: placing RBS beams in cantilevers, not removing the backing plate under the bottom skid of the beam, poor design of the shear plate, placing lateral bracing or other elements in the protected zone of the beam, among other errors, and subsequently, a detailed analysis of the mistake was made, with possible consequences that may result, accompanied by a photo of the error and what should have been done according to the codes. In addition, since there is no constructive procedure for this connection in the normatives and codes, it was developed very detailed based on field observation and recommendations from American codes. The procedure was validated through a survey of experts on the subject and they agreed that it is clear, concise and can even be used on site.